Simultaneous lesions of complex odontoma associated with dentigerous cyst: case report and critical review in CBCT - Hidayat, Muhammad Fadil; Tenrilili, Andi Nurul Azizah; Yunus, Barunawaty (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2024)
Objectives: To our knowledge, there is limited evidence reporting cystic lesions associated with odontoma. Therefore, this case report aims to describe the clinical, histological, and particularly the characteristic cone beam computed tomography (CBCT) diagnostic features . Case Report: A 20-year-old male patient presented with a complaint of a lump in the upper right jaw. There was no history of systemic disease. A panoramic radiograph showed a solid radio-opaque mass surrounded by an osteolytic lesion with a radio-opaque margin causing impaction of the maxillary canine. Given the limitations of panoramic radiography in assessing lesion extent, a CBCT examination was performed. Multiplanar reconstruction revealed a well-defined unilocular hyperdense lesion with a hypodense encapsulation and corticated margin, measuring 31.5 x 32 mm, expanding the buccal cortical plate and pushing the upper right canine tooth into the maxillary sinus cavity. The extensive expansion of the lesion required histopathological analysis to confirm the final diagnosis. The histopathological examination concluded a dentigerous cyst. Conclusion: Several reports in the literature discuss the development of cysts and tumors in the jaw, but some cases are very difficult to identify. The variability of lesions can complicate pattern identification, leading to misinterpretation of conventional radiographs, thus requiring additional CBCT evaluation.